Enzymatic hydrolysis of spent Saccharomyces cerevisiae derived from sago bioethanol fermentation - Nik Nur Aziati, Mahmod; Nurashikin, Suhaili; Awang Ahmad Sallehin, Awang Husaini; Dayang Salwani, Awang Adeni; Siti Efliza, Ashari (World Researchers Associations, 2023)
Spent Saccharomyces cerevisiae is a by-product of bioethanol fermentation. The spent yeast is abundant in valuable components which can be used for many applications. One of the ways to prepare yeast extract is through enzymatic hydrolysis which is by rupturing the yeast cell walls using exogenous enzymes under certain conditions that promote the leakage of intracellular compounds. To date, enzymatic hydrolysis of spent S. cerevisiae derived from the production of sago bioethanol is yet to be thoroughly explored. In the present study, we examine the feasibility of enzymatic hydrolysis of spent S. cerevisiae generated from sago bioethanol fermentation. The effect of two enzymes namely alcalase and cellulase and their concentrations (0.1-0.5% (v/v) on the release of protein and carbohydrate in the hydrolysate was also investigated. Additionally, the surface morphology of the hydrolysed yeast cells was observed using a Scanning electron microscope (SEM). Our results showed that the optimal concentration of alcalase and cellulase for enzymatic hydrolysis of spent S. cerevisiae was 0.4% (v/v) and 0.5% (v/v) respectively. In addition, cellulase was found to be more superior than alcalase with respect to the protein content in the hydrolysate. The enzymatic hydrolysis of spent yeast by alcalase and cellulase yielded improvements of 1.1 to 1.8-fold and 3.5 to 5.6-fold of protein and total carbohydrate concentration respectively in comparison to that achieved via autolysis. It was evident from the SEM analysis that there was a notable change in the surface morphology of the lysed yeast cells indicating the lysis of the yeast cells throughout the enzymatic hydrolysis. In summary, the current work provides useful insights into the strategies of valorising spent S. cerevisiae generated from sago bioethanol production. This will further help the development of value-added products from the waste, hence promoting a sustainable economy besides reducing the environmental impacts associated with the disposal of spent S. cerevisiae.